ANALISIS PENGARUH KECERDASAN ADVERSITAS,INTERNAL LOCUS OF CONTROL, KEMATANGAN KARIR TERHADAP INTENSI BERWIRAUSAHA PADA MAHASISWA BEKERJA - Srimulyani, Veronika Agustini (Widya Warta, 2013)
The young generation including students is considered as the agent of development change. Students are one of the potential resources that own knowledge and competence better than high school or vocational school graduates. Entrepreneurship is an alternative option that is quite appropriate for students to develop their potential. Entrepreneurial intentions can be affected by adversity intelligence, internal locus of control, and career maturity. This study aims toobtain empirical evidence on the effects of adversity intelligence, internal locus of control, and career maturity toward entrepreneurial intensions with worker students as its respondents. The number of the respondents of this study is 49 students from the employee classof the management department, accountingdepartment, guidance and counselingdepartment, and psychology department. The data analysis technique applied here is multiple linear regression analysis using SPSS software version 17. The results of either partial or simultaneous test prove that adversity intelligence, internal locus of control, and career maturity have a significant positive effect on entrepreneurial intentions.